2011
DOI: 10.1002/adv.20211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packing pressure on refractive index variation in injection molding of precision plastic optical lens

Abstract: ABSTRACT:In this study, refractive index variation in injection-molded polymethylmethacrylate optical lenses under different levels of packing pressure was evaluated using a Shack-Hartmann wavefront sensor-based metrology system. The experimental results showed that optical polymer's refractive index exhibits a considerable amount of variation for the lenses molded under different packing pressures. Specifically, within the range investigated in this study, refractive index variation is more uniform when highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…This is an effective packing with high packing pressure and long packing time. Thus, compared with previous studies [5,7], the distribution variation is relatively small with a maximum deviation of 6 × 10 −4 . In addition to the small deviation, because higher packing pressure occurs closer to the injection gate, the general trend of the distribution decreases along the flow direction.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…This is an effective packing with high packing pressure and long packing time. Thus, compared with previous studies [5,7], the distribution variation is relatively small with a maximum deviation of 6 × 10 −4 . In addition to the small deviation, because higher packing pressure occurs closer to the injection gate, the general trend of the distribution decreases along the flow direction.…”
Section: Resultscontrasting
confidence: 66%
“…The geometric deformation primarily has an impact on optical refraction, so the nodes' positions on the top and bottom surface meshes were extracted for numerical analysis of its optical aberrations in the next section. Furthermore, uneven cooling as well as the polymer's rheological properties could result in an unevenly distributed density that consequently causes variation in refractive index [7]. Therefore, refractive index information at each node was also collected for optical aberration analysis.…”
Section: B Injection Molding Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This measurement was performed in a field of 126 μ m × 96 μ m, with a best-fit spherical surface removed from the measurement. To form an optical surface, the roughness should be 10 to 20 times smaller than the light wavelengths [ 26 ]. For this measurement, the arithmetical mean roughness ( R a ) is 4.77 nm, the root mean square roughness ( R q ) is 6.31 nm, and the total height of the roughness ( R t ) is 234.89 nm.…”
Section: Micro Surface Roughnessmentioning
confidence: 99%
“…Shibuya used COC and COP as materials and demonstrated that optical retardation of the sensor lens became high if the birefringence of materials was high, and reported that environmental stress degraded the resolution [6]. Yang et al used PMMA as a material and reported that the filling pressure at the molding process of the optic plastic lens influences the refractive index profile of the molded parts [7].…”
Section: Introductionmentioning
confidence: 99%